Adaptation of Student Engagement in Mathematics Scale into Turkish (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The purpose of this study is to adapt “Student Engagement in Mathematics Scale”, developed by Rimm-Kauffman (2010), into Turkish and to determine validity and reliability of the scale in Turkish form. The study group is consisted of 602 secondary school students. The original scale consisted of 13 items with three factors (social, emotional and cognitive). Adapted scale’s test-retest reliability coefficient was found .591 and Cronbach alpha value was found .872. Item-total correlations of scale items ranged between .30 to .66. First order and second order confirmatory factor analyses were executed for construct validity. As a result of confirmatory factor analyses, the scale was confirmed consisting of three factors namely “social”, “cognitive” and “emotional” as in original scale. These results showed that Turkish form of the scale, being reliable and valid, can be used in studies related to mathematics engagement.